Influence of thermal-oxidative aging on the mechanical performance and structure of cold-mixed epoxy asphalt. (20th February 2022) - Si, Jingjing; Wang, Junyan; Yu, Xin; Ding, Gongying; Ruan, Wei; Xing, Miaomiao; Xie, Renxuan
Abstract: High temperature and oxidation are two of the most critical factors that cause epoxy asphalt aging. This paper aims to clarify the variation of mechanical performance and structure of effect of cold-mixed epoxy asphalt (CEA) after thermal-oxidative (TO) aging. The mechanical properties of CEA were studied by tensile tests and dynamic mechanical analysis. The microstructure of CEA was studied by Fourier transform infrared spectrum, X-ray photoelectron spectroscopy, SEM, and fluorescence microscopy. The results indicated that the tensile strength of CEA increased to 5.16 MPa, the elongation at break decreased to 50.3%, and the T g decreased significantly after TO aging. TO aging made the epoxy resin in CEA post-cure, oxidate, degrade and the cross-linked network break. Furthermore, the asphalt particles in CEA agglomerated and oxidized. Graphical abstract: Image 1 Highlights: ER underwent a post-curing reaction and degradation. Asphalt underwent volatilization of the light components and an oxidation reaction. Thermal-oxidative aging destroyed the original phase structure of the CEA.